Development of a medication experience scale for patients with chronic disease in primary care facilities - Jiaxian Shao; Haihong Cao; Zhihong Sun; Xiaona Li; Min Gao; Ziyuan Li; Yongli Shi; Ping Dong; Wenqiang Yin; Zhongming Chen (Chinese General Practice Journal)
Background: Understanding patients' medication experience is crucial for improving adherence, health outcomes, and medical safety. Currently, there is a lack of measurement tools for the medication experience of patients with chronic diseases in primary care facilities in China, which seriously restricts the research and practice of pharmaceutical service and management in primary care facilities. Objective: This study aims to develop the Medication Experience Scale For Patients with Chronic Disease in Primary Care Facilities tailored to China's chronic disease management practices. The scale is intended to support research and practice in medication management for chronic disease patients. Methods: A preliminary item pool for the scale was constructed through literature review, semi-structured interviews, and focus group discussions. The Delphi Method was employed to consult experts and refine the scale. A pilot survey was conducted with 313 chronic disease patients from primary care facilities, selected via random sampling. The reliability and validity of the scale were tested, and iterative adjustments were made to optimize its content. Results: The finalized scale consists of 3 primary dimensions, 7 secondary dimensions, and 28 measurement items. Item analysis yielded P-values < 0.05. The Cronbach's α coefficients for the overall scale and all dimensions exceeded 0.8, with split-half reliabilities above 0.7 and intra-class correlation coefficients above 0.8, indicating high reliability. Post-rotation factor loadings for all items exceeded 0.5. The confirmatory factor analysis demonstrated excellent model fit: CMIN/DF = 1.485, GFI = 0.902, RMSEA = 0.039, RMR = 0.03, CFI = 0.981, NFI = 0.945, IFI = 0.981. Composite reliability values were above 0.7, and average variance extracted values exceeded 0.5, demonstrating strong validity. Conclusion: The Medication Experience Scale For Patients with Chronic Disease in Primary Care Facilities developed in this study exhibits better reliability and validity. Its adaptability to local contexts make it a suitable tool for investigating the medication experiences of chronic disease patients in primary care facilities.